Soft tissue reconstruction with anterior pedicled inferior turbinate flap in conjunction with palatal flap for standard inferior maxillectomy with hard palate resection. Issue 5 (5th February 2020) - Omura, Kazuhiro; Nomura, Kazuhiro; Aoki, Satoshi; Otori, Nobuyoshi; Tanaka, Yasuhiro
Abstract: Background: The defect after surgical resection of sinonasal malignant tumors is normally reconstructed using free flaps obtained from donor sites. There is no report of using the palatal island flap to reconstruct defects after surgery. We aimed to describe our technique of soft tissue reconstruction through anterior pedicled inferior turbinate (APIT) flap in conjunction with palatal flap for standard inferior maxillectomy with hard palate resection and its outcomes and to discuss its advantages and disadvantages compared with free‐flap reconstruction. Methods: For resection of malignant tumors arising from the anterior nasal septum, we preserved the hard palate during maxillectomy using a palatal island flap and an anterior pedicled inferior turbinate flap. Results: One patient developed a small oroantral fistula, which was sealed with a denture. The other patient had a good outcome. Conclusion: Our technique of maxillectomy is useful for selected cases of sinonasal malignancy that require maxillary floor resection.